ANALISIS ISI: KARAKTERISTIK TEKS DALAM BUKU BAHASA INDONESIA PEGANGAN SISWA SMA - Dudu Mawarida Sembiring; Eko Kuntarto; Andiopenta Purba (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2023)
The research aims to identify the characteristics of the text in teaching materials in the form of Indonesian language textbooks for class XI students of junior high school. The type of text chosen is procedure text, Lectures, Short Stories, and Dramas on the basis of the choice that there is a new paradigm of language and text, curriculum development, the need to optimize learning references for teachers and students, the importance of improving students' analytical abilities, and to see the extent of feasibility use of these teaching materials. The research method is content analysis of the collected literature. Covers key aspects of reading and writing skills and assessment. Is a type of descriptive analysis with a type of qualitative research. Research as a tool is a collection of someone's writings in the form of hardcopy/softcopy so that they are in the form of a grid. The results of the data analysis showed that there were differences between the substance of the text content and the students' social backgrounds, and there were errors/errors/negligence in the preparation/presentation of the text, such as the use of punctuation marks. conjunctions, contradictions between titles and contents, and so on. So it is recommended to review